Pro-inflammatory cytokine interleukin-1β promotes the development of intestinal stem cells - Wang, Lei; Liu, Ziyan; Li, Yijing; Pappan, Loretta; Galliher-Beckley, Amy; Shi, Jishu N. (My University, 2012)
Objective: We investigated the effect of IL-1β on the development of intestinal epithelial stem cells. Materials and methods: Normal intestinal epithelial cell line IEC-18 cells were cultured in the presence or absence of 200 pM of IL-1β in serum-free medium (SFM) for various time periods. The effects of IL-1β on intestinal stem cell self-renewal and IEC-18 cell proliferation were evaluated by a colony formation assay, MTT assay, and a focus formation assay. The expression of stemness genes including Bmi-1, Lgr-5, c-myc, Nanog, and β-catenin in IEC-18 cells were measured by quantitative PCR and western blot analysis. Results: IEC-18 cells grew as a monolayer in SFM in the absence of IL-1β. Cellular spheres were formed when IEC-18 cells were grown in SFM in the presence of IL-1β. IL-1β induced the development of large colonies in the soft-agar as well as the formation of foci when IEC-18 cells were cultured in type-I collagen-coated plates. The expression of Bmi-1, Lgr-5, c-myc, Nanog, and β-catenin were significantly increased in IEC-18 cells treated with IL-1β. Conclusion: Our studies provide direct evidence the IL-1β may play an important role in the self-renewal of intestinal epithelial stem cells and the development of cancer stem cells.
Keywords: IL-1β; Stem cells; Intestinal epithelial; IEC-18; Cancer; Self-renewal